Analisis Pengaruh Energi Dan Protein Ransum Terhadap Feed Conversion Ratio (FCR) Ayam Broiler Di Wilayah Lahan Kering Tropis: Kajian Literatur - Maria Kristina Sinabang (CV. SINAR HOWUHOWU, 2026)
Broiler chickens are a strategic poultry commodity as the primary source of animal protein in Indonesia; however, their production efficiency—measured by the Feed Conversion Ratio (FCR)—faces serious challenges in tropical dryland regions due to extreme temperatures of 28°C–34°C, which trigger heat stress and impair nutrient absorption. This study aims to evaluate the effect of Metabolizable Energy (ME) and Crude Protein (CP) levels in the diet on the FCR of broiler chickens in tropical dryland areas. The study employed a Systematic Literature Review (SLR) approach and descriptive statistics on secondary data from six scientific articles obtained via the Google Scholar database, with inclusion criteria covering studies from 2016 to 2026, conducted at temperatures of 28°C–34°C, and fully reporting the variables ME, CP, and FCR. Data were analyzed using multiple linear regression with the model Y = a + b₁X₁ + b₂X₂ + e, tested via the F-test and t-test at a 95% confidence level. Results indicated that EM and PK simultaneously had a significant effect on FCR (F = 9.577; p = 0.003) with R² = 0.596. The resulting regression equation is Y = 5.160 – 0.001X₁ – 0.079X₂, where PK exerts a more dominant influence (coefficient -0.079; p = 0.008) compared to EM (coefficient -0.001; p = 0.043) in reducing FCR. An innovative Black Soldier Fly larvae meal feed formulation containing EM, with 3,157.32 kcal/kg and 22.22% crude protein, was able to reduce the FCR to 0.98; however, extreme temperatures caused some of the energy to be allocated toward thermoregulation. It was concluded that an adaptive balance between energy and protein ratios is a crucial factor in maintaining feed efficiency in broiler chickens in tropical dryland regions.